2018
DOI: 10.1111/ajt.15005
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation in foreign nationals: Lower rates of waitlist mortality and higher rates of lost to follow-up posttransplant

Abstract: A controversial issue in the transplant community is whether or not to provide deceased donor liver transplantation (DDLT) to noncitizen/nonresidents (NCNRs) who travel for liver transplantation (LT). The expectation is that transplantation of NCNRs will not compromise access for US citizens/residents (USCRs), and that NCNRs would have similar post-LT follow-up. This has never been formally assessed. The United Network for Organ Sharing (UNOS) data from February 27, 2002 to December 31, 2016 were used to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 5 publications
(2 reference statements)
2
16
0
Order By: Relevance
“…Indeed, without distinguishing transplant tourists from unauthorized immigrants, the non-US citizens/ non-US resident group in LT has been described as predominantly of high socioeconomic class, from Gulf countries (e.g., Saudi Arabia, United Arab Emirates, Kuwait, and so on), and with worse post-LT survival. (6,7) With our exclusion criteria to identify presumed unauthorized immigrants, we found that non-US citizen/non-US resident LT recipients in our study reflect the general US unauthorized immigrant population and are predominantly from Latin America. More importantly, contrary to a study examining non-US citizens/non-US residents that included transplant tourists, (6) our study found that patient survival was similar between non-US citizens/non-US residents and residents when excluding transplant tourists.…”
Section: Figmentioning
confidence: 74%
See 4 more Smart Citations
“…Indeed, without distinguishing transplant tourists from unauthorized immigrants, the non-US citizens/ non-US resident group in LT has been described as predominantly of high socioeconomic class, from Gulf countries (e.g., Saudi Arabia, United Arab Emirates, Kuwait, and so on), and with worse post-LT survival. (6,7) With our exclusion criteria to identify presumed unauthorized immigrants, we found that non-US citizen/non-US resident LT recipients in our study reflect the general US unauthorized immigrant population and are predominantly from Latin America. More importantly, contrary to a study examining non-US citizens/non-US residents that included transplant tourists, (6) our study found that patient survival was similar between non-US citizens/non-US residents and residents when excluding transplant tourists.…”
Section: Figmentioning
confidence: 74%
“…(6,7) With our exclusion criteria to identify presumed unauthorized immigrants, we found that non-US citizen/non-US resident LT recipients in our study reflect the general US unauthorized immigrant population and are predominantly from Latin America. More importantly, contrary to a study examining non-US citizens/non-US residents that included transplant tourists, (6) our study found that patient survival was similar between non-US citizens/non-US residents and residents when excluding transplant tourists. Although we found a higher likelihood of being lost to follow-up among presumed unauthorized immigrants, this finding should be interpreted with caution, as it was based on only seven events.…”
Section: Figmentioning
confidence: 74%
See 3 more Smart Citations